INFLUENCE OF THE RESPIRATORY SIGNAL IN HEART RATE VARIABILITY ANALYSIS IN THE RESPIRATORY PATTERN IN HEALTHY ELDERLY AND WITH COPD - Materko, Wollner; Bartels, Rhenan; Motta-Ribeiro, Gabriel Casulari; Lopes, Agnaldo José; Nadal, Jurandir; SilvaCarvalho, Alysson Roncally (International Journal of Engineering Technologies and Management Research, 2018)
Motivation/Background: Cardiorespiratory interaction is known to cause a peak in the heart rate variability (HRV) spectrum, characterized as sinus arrhythmia. This study evaluates standard indexes of HRV spectral analysis with and without the influence of respiratory signal in elderly subjects with chronic obstructive pulmonary disease (COPD, N=14) and healthy lungs (N=14). In the last, all subjects controlled their breathing at 0.1 Hz (CGL) and breathed freely (CG). Method: Anthropometrical characteristics were similar, with increased heart rate in COPD (75±11.1 vs. 62±8.3 bpm). Cardiac and respiratory signals in supine position were recorded with a portable data acquisition system during 5 min and processed in frequency domain. To remove the influence of the respiration in HRV, a 2th order Butterworth band-stop filter, was applied to the RRi signal. Results: In CGL main respiratory frequency was significantly lower (ANOVA with post-hoc Turkey's test, α = 0.05) and with the influence of respiratory signal differed from without the influence of respiratory signal to HRV spectral analysis (Student t-test, α = 0.05) with increased low frequency contribution (51.0±11.4 vs. 42.0±11.6, respectively). PG and CG showed no significant differences in with or without influence of respiratory signal to HRV spectral analysis. Conclusions: The results of the present study have showed a low frequency respiration at 0.1 Hz provided an increase in low frequency and decrease in high frequency power spectral analysis, showing an error in the HRV analysis.